A node splitting interface algorithm for multi-rate parallel simulation of DC grids - Mu, Qing; Liang, Jun; Zhou, Xiaoxin; Li, Gen; Zhang, Xing (CSEE Journal of Power and Energy Systems, 2018)
With wider applications of power electronic devices in modern power systems, simulation using traditional electromechanical and electromagnetic simulation tools suffer from low speed and imprecision. Multi-rate technologies can greatly improve simulation efficiency by avoiding simulating the entire system using a small time-step. However, the drawbacks of the current synchronization mechanisms is that they introduce numerical errors and numerical instabilities in multi-rate parallel simulations. An improved multi-rate parallel technology, node splitting interface (NSI), is proposed to reduce errors and enhance simulation stability. A new synchronization mechanism is used to avoid prediction and signal delays. Theoretical analyses are carried out to prove the convergence and absolute stability of the proposed NSI algorithm. This algorithm is particularly suitable for simultaneously investigating long term dynamics of DC grids and fast transients of power electronic converters.